(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: This paper examines colonialism and imperialism as interrelated systems that shaped India’s political, economic, social, and cultural landscapes from the seventeenth to the twentieth century. By analysing the British colonial enterprise and its underlying imperial ideology, the study explores how domination was institutionalized through governance structures, economic exploitation, and cultural hegemony. Drawing on historical records, postcolonial theory, and economic analyses, the paper argues that colonialism in India functioned not merely as political occupation but as a comprehensive system of control designed to sustain imperial power. It highlights the mechanisms through which colonial policies restructured India’s economy, disrupted indigenous industries, and redefined social hierarchies. Furthermore, the research investigates the lasting legacies of imperialism in contemporary Indian society, economy, and identity formation. Ultimately, this paper situates India’s colonial experience within the broader global context of imperial systems, offering insights into how resistance movements and nationalist discourses emerged as counter-systems challenging colonial domination.